Ionization of He, Ne, Ar, Kr, and Xe by proton impact: Single differential distributions in energy and angles - Miraglia, Jorge Esteban (2009)
In this paper we report energy and angular distributions of electrons emitted in collisions of protons with neon- F− ,Ne0 ,Na+, argon- Cl− ,Ar0 ,K+, krypton- Br− ,Kr0 ,Rb+, and xenon- I − ,Xe0 isoelectronic series for high and intermediate impact energies. Calculations were performed within the continuum distorted waveeikonal initial-state method using an angular expansion in spherical harmonics and a numerical evaluation of the radial functions corresponding to both: the initial bound and the final continuum states in the same central potential. The first Born approximation was calculated on equal footing. The shellwise local plasma approximation was also calculated when possible. A complete and exhaustive comparison with the available experimental data is carried out. We have spanned almost all the published experiments in our range of interest. Successes and failures of the different theoretical methods are pointed out. Possible signatures of manyelectron effects are noticed.